Additive effects of blood donor smoking and gamma irradiation on outcome measures of red blood cell transfusion. Issue 6 (1st May 2020) - DeSimone, Robert A.; Plimier, Colleen; Lee, Catherine; Kanias, Tamir; Cushing, Melissa M.; Sachais, Bruce S.; Kleinman, Steven; Busch, Michael P.; Roubinian, Nareg H.
Abstract : BACKGROUND: Recent publications have reported conflicting results regarding the role of blood donor tobacco use on hemoglobin (Hb) levels in patients after red blood cell (RBC) transfusion. We examined associations and interactions between donor, component, and recipient factors to better understand the impact of donor smoking on transfusion outcomes. STUDY DESIGN AND METHODS: We linked blood donor and component manufacturing data, including self‐reported cigarette smoking, with a cohort of patients transfused RBCs between 2013 and 2016. Using multivariable regression, we examined Hb increments and subsequent transfusion requirements after single‐unit RBC transfusion episodes, adjusting for donor, component, and recipient factors. RESULTS: We linked data on 4038 transfusion recipients who received one or more single‐unit RBC transfusions (n = 5086 units) to donor demographic and component manufacturing characteristics. Among RBC units from smokers (n = 326), Hb increments were reduced after transfusion of gamma‐irradiated units (0.76 g/dL; p = 0.033) but not unirradiated units (1.04 g/dL; p = 0.54) compared to those from nonsmokers (1.01 g/dL; n = 4760). In parallel with changes in Hb levels, donor smoking was associated with the receipt of additional RBC transfusions for irradiated (odds ratio [OR], 2.49; p = 0.01) but not unirradiated RBC units (OR, 1.10; p = 0.52). CONCLUSION: Donor smoking was associated with reduced Hb increments and the need for additional transfusions in recipients of gamma‐irradiated RBC units. Additional research is needed to better understand interactions between donor, component, and recipient factors on efficacy measures of RBC transfusion.